PENGARUH MOTIVASI, PENDIDIKAN KEWIRAUSAHAAN DAN LINGKUNGAN KELUARGA TERHADAP MINAT BERWIRAUSAHA MAHASISWA - nurmalasari nurmalasari; latifah latifah (STIE 'INDONESIA' Pontianak, 2022)
This study aims to determine how the influence of motivation, entrepreneurship education and family environment on students' interest in entrepreneurship. This research uses quantitative analysis with data collection method used is simple random sampling method. Respondents are students who are taking Entrepreneurship courses at the University of Bina Sarana Informatika, Pontianak Campus. Collecting data using a questionnaire, namely by distributing a list of questions using Google Form to respondents. The research model that will be used in this study is a regression analysis model to test the proposed hypothesis using the Multiple Linear Regression technique using the SPSS program. The results of the regression test showed that there was an influence between motivation, entrepreneurship education, and family environment simultaneously or partially on students' interest in entrepreneurship. Overall, we can conclude that the hypothesis which reads that there is an influence between motivation, entrepreneurship education, and family environment on students' interest in entrepreneurship is acceptable.